Vascularised Epiphysis and Hemi-Joint Transfer for Reconstruction of Temporomandibular Joint and Ramus-Condyle Unit in Cases of Hemifacial Microsomia - A K Gupta; A P Chitre; S Abhyankar (Indian Journal of Plastic Surgery)
Epiphysis and hemi-joint transfer for reconstruction of the temporomandibular joint and ramus-condyle unit, using the proximal epiphyseal plate and proximal one third of the diaphyseal shaft of the fibula has been successfully performed in cases of hemifacial macrosomia. A total of 6 cases belonging to the type II and III of skeletal type of hemifacial microsomia1 in the age group of 3 to 8 years have undergone this procedure. All patients have a good range of painless movement at the temporomandibular joint with a proportionate growth of 0.4 cms and 0.5 cms per year respectively at the neo ramus condyle unit and they have been illustrated.